2016
DOI: 10.1016/j.ijppaw.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Mussels ( Perna perna ) as bioindicator of environmental contamination by Cryptosporidium species with zoonotic potential

Abstract: Sources of contamination such as animal feces runoff, organic fertilizer application, and the release of partially treated or untreated sewage can lead to the contamination of aquatic environments by Cryptosporidium spp. The quality of mussels as food is closely related to the sanitary conditions of the marine environment where these bivalves are found. Marine mollusks are filter feeders that are able to retain Cryptosporidium oocysts in their tissue, thus functioning as bioindicators. A total of 72 pooled mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 36 publications
0
5
0
5
Order By: Relevance
“…Cryptosporidium is not only present in vegetables and fruits, but also in other foods, like dairy products, meat, or shellfish (reviewed in [ 18 ]). Many studies have demonstrated the presence of this protozoan in shellfish (i.e., [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]). Shellfish filter and accumulate Cryptosporidium oocysts from water, which proves that Cryptosporidium is present in different water sources, including estuarine and coastal ecosystems.…”
Section: Cryptosporidium Sppmentioning
confidence: 99%
“…Cryptosporidium is not only present in vegetables and fruits, but also in other foods, like dairy products, meat, or shellfish (reviewed in [ 18 ]). Many studies have demonstrated the presence of this protozoan in shellfish (i.e., [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]). Shellfish filter and accumulate Cryptosporidium oocysts from water, which proves that Cryptosporidium is present in different water sources, including estuarine and coastal ecosystems.…”
Section: Cryptosporidium Sppmentioning
confidence: 99%
“…El protozoario más importante en la casuística de patología gastrointestinal, como lo es Giardia spp, se encontró en un 30%. Este parásito se ha reportado en mariscos de países asiáticos, europeos y norteamericanos (Robertson, 2007;Gómez-Couso & Ares-Mazás, 2012;Oliveira et al, 2016;Ghozzi et al, 2017;Ligda, 2019;Tedde et al, 2019) como así también Santos et al (2018) lo han reportado en Brasil. Nuestros resultados son coincidentes con los reportados en otros países y constituyó el primer reporte de Giardia spp en M. edulis en Argentina (Torrecillas et al, 2019).…”
Section: Confirmación De Quistes Deunclassified
“…Existen reportes sobre la presencia de parásitos en moluscos bivalvos tales como Mytilus galloprovincialis, Oestrea edulis, Mytilus edulis, entre otros, que acumulan ooquistes de Cryptosporidium spp y quistes de Giardia spp en otros lugares del mundo (Oliveira et al, 2016;Ghozzi et al, 2017;Tedde et al, 2019). Existen trabajos previos en Argentina, donde se ha reportado la presencia de parásitos de la familia Gymnophalydae que presentan potencial zoonótico en bivalvos de otras regiones (Vázquez et al, 2018).…”
unclassified
“…Naegleria fowleri , the only pathogenic Naegleria species which is associated with primary amoebic meningoencephalitis, has not been detected to date in the Ebro River reservoirs (Garcia et al ., 2013). The microbial community inside mussels and other bivalves is closely related to the microbiological composition of the environment in which they are attached (Mariné Oliveira et al ., 2016). FLAs are usually integrated into biofilms, which correspond to complex structures where microorganisms are associated (Castrillon Rivera and Palma‐Ramos, 2012).…”
Section: Introductionmentioning
confidence: 99%